Pancasila Sebagai Ideologi Bangsa Dalam Perspektif Islam - M. Argian Naufal; Alvin Ryshakti (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This research aims to analyze the role of Pancasila as a state ideology from an Islamic perspective. Pancasila as the basis of the Indonesian state describes basic principles that include social, political and religious values. The Islamic perspective plays an important role in this framework, because the majority of the Indonesian population is Muslim and Islam plays a central role in their lives. This study explores the relationship between Pancasila principles and Islamic values, and how the two can coexist to achieve an inclusive and sustainable national ideology. This research uses documentary analysis methods, interviews and document research to gain a deeper understanding of the Islamic perspective on Pancasila. The research results show that in Pancasila there are elements that are in line with Islamic values such as social justice, solidarity and humanity. However, there are also differences in views regarding the application and interpretation of these values. This study provides important insights into how Pancasila can be interpreted in an Islamic context, which has a major impact on the ideological identity of the Indonesian nation. This research also examines the political and social implications of the relationship between Pancasila and Islam, as well as its impact on pluralism and social harmony in Indonesia.